Endocrine disruptor (17 β-estradiol) removal by poly pyrrole-based molecularly imprinted polymer: kinetic, isotherms and thermodynamic studies - Samaneh Mohebbi; Aram Dokht Khatibi; Davoud Balarak; Maryam Khashij; Edris Bazrafshan; Mohammad Mehralian (Applied Water Science)
Abstract This study focuses on the synthesis and characterization of the molecularly imprinted polymer (PPy-MIP) to remove 17β-Estradiol (E2) from aqueous solutions. The MIP was synthesized using a non-covalent procedure, incorporating the target compound, E2. To synthesis PPy-MIP, a mixture of 300 μl pyrrole and 50 ml distilled water was stirred for 30 min. After adding 3 g ferric chloride as an oxidant, the solution was mixed for 2 h and stored for 48–72 h. MIP capability is compared with a non-molecularly imprinted polymer (NIP) as a control. Various factors such as pH, contact time, dosage, temperature, and concentration were investigated to optimize the performance of the PPy-MIP. The structure of the MIP was confirmed using field emission scanning electron microscopy (FESEM), infrared spectrophotometric spectrum (FTIR), and X-ray diffraction (XRD). The efficiency of the PPy-MIP in removing E2 was obtained 99.97% at optimum condition; while, the NIP achieved a removal efficiency of 69.9%. Adsorption data were fitted with Langmuir isotherms (R 2 0.98) and pseudo-second-order kinetics (R2 0.99). The selectivity of the PPy-MIP toward similar compounds such as progesterone and cholesterol was also examined. To understand the adsorption process, thermodynamics, kinetics, and isotherm studies were performed. The MIP showed good reproducibility with only a slight decrease in removal efficiency after multiple absorption and reabsorption cycles. The adsorption of E2 by the MIP followed Langmuir adsorption isotherm and second-order adsorption kinetics. MIP was utilized to pre-concentrate and separate E2 in real samples (urine, blood, hospital wastewater, tap water). This method shows promise for efficient and selective removal of E2 from aqueous solutions.